Glutamine synthetase expression rescues human dendritic cell survival in a glutamine-deprived environment - Schoeppe, Robert; Babl, Nathalie; Decking, Sonja-Maria; Schönhammer, Gabriele; Siegmund, Andreas; Bruss, Christina; Dettmer, Katja; Oefner, Peter J.; Frick, Linus; Weigert, Anna; Jantsch, Jonathan; Herr, Wolfgang; et al. (Frontiers in Oncology, 2023)
Introduction Glutamine deficiency is a well-known feature of the tumor environment. Here we analyzed the impact of glutamine deprivation on human myeloid cell survival and function. Methods Different types of myeloid cells were cultured in the absence or presence of glutamine and/or with L-methionine-S-sulfoximine (MSO), an irreversible glutamine synthetase (GS) inhibitor. GS expression was analyzed on mRNA and protein level. GS activity and the conversion of glutamate to glutamine by myeloid cells was followed by 13C tracing analyses. Results The absence of extracellular glutamine only slightly affected postmitotic human monocyte to dendritic cell (DC) differentiation, function and survival. Similar results were obtained for monocyte-derived macrophages. In contrast, proliferation of the monocytic leukemia cell line THP-1 was significantly suppressed. While macrophages exhibited high constitutive GS expression, glutamine deprivation induced GS in DC and THP-1. Accordingly, proliferation of THP-1 was rescued by addition of the GS substrate glutamate and 13C tracing analyses revealed conversion of glutamate to glutamine. Supplementation with the GS inhibitor MSO reduced the survival of DC and macrophages and counteracted the proliferation rescue of THP-1 by glutamate. Discussion Our results show that GS supports myeloid cell survival in a glutamine poor environment. Notably, in addition to suppressing proliferation and survival of tumor cells, the blockade of GS also targets immune cells such as DCs and macrophages.